Bulk superconducting materials as a tool for control, confinement, and accumulation of polarized substances: the case of MgB2 - Ciullo, G.; Barion, L.; Contalbrigo, M.; Del Bianco, L.; Lenisa, P.; Spizzo, F.; Statera, M.; Tagliente, G. (Frontiers in Physics, 2024)
Providing strong magnetic holding fields, while at the same time guaranteeing shielding from unwanted external fields, is a key requirement for the accumulation, preservation and transport of nuclear polarized materials: it is a crucial achievement for its exploitation in fusion test facilities and in particle physics. High-temperature bulk superconducting materials represent an innovative and promising solution, as they are easily machinable and they can be cooled down by a cold-head. This work considers a bulk MgB 2 superconducting hollow cylinder and the successful preliminary studies, performed by measuring trapped fields in the order of one tesla in its center, encouraged to upgrade the prototype apparatus for deep insight knowledges. The new system allows to work at lower temperature 8 K, to exchange cylinders and come back in working condition in one day, to map the transverse fields along the radial coordinate (in 11 mm) and along the symmetry axis (in 48 mm): it allows then to find the proper geometry and the production procedure for its use in fusion test facility. The commissioning of the upgraded system provides results already useful for its use for polarized fusion fuel, for instance as holding field for recombined hyper-polarized molecules from the recombination of atomic polarized beams, but it gives, also, the possibility to investigate the use of MgB 2 in nuclear polarized nuclear targets.